2014
DOI: 10.4103/0971-6203.139001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the dosimetric accuracies of CATPhan 504 and CIRS 062 using kV-CBCT for performing direct calculations

Abstract: The dosimetric accuracies of CATPhan 504 and CIRS 062 have been evaluated using the kV-CBCT of Varian TrueBeam linac and Eclipse TPS. The assessment was done using the kV-CBCT as a standalone tool for dosimetric calculations towards Adaptive replanning. Dosimetric calculations were made without altering the HU-ED curves of the planning computed tomography (CT) scanner that is used by the Eclipse TPS. All computations were done using the images and dataset from kV-CBCT while maintaining the HU-ED calibration cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…In many studies, customised protocols were chosen [37,40,107,41,47,48,55,58,66,75,104], adding extra variables to be considered when comparing the techniques adopted to perform CBCT dose calculation. Therefore, site-specific protocols for each machine model cannot be specified in this review for an optimal CBCT dose calculation.…”
Section: Physical Limitationsmentioning
confidence: 99%
“…In many studies, customised protocols were chosen [37,40,107,41,47,48,55,58,66,75,104], adding extra variables to be considered when comparing the techniques adopted to perform CBCT dose calculation. Therefore, site-specific protocols for each machine model cannot be specified in this review for an optimal CBCT dose calculation.…”
Section: Physical Limitationsmentioning
confidence: 99%
“…In this study, a self-developed tool, the cone-beam CT imaging toolkit (CITK), was used for CBCT image scatter correction. This tool considers the interaction between the particles and the substance in the Monte Carlo (MC) simulation and separates the scattering components from the original CBCT projection files ( 19 , 27 ), realizing CBCT image scattering correction.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the computed tomography (CT) value [in Hounsfield units (HU)] of CBCT images was significantly different from that of planning CT (pCT) images. Annkah et al ( 19 ) found that the maximum dose difference reached 14% in a phantom. Therefore, establishing appropriate HU-relative electron density (HU-RED) calibration for CBCT images is critical for clinical dose calculations ( 17 - 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that X-ray photons are mainly attenuated by interactions with atomic shell electrons, the tissue-specific attenuation coefficient is strongly correlated to the local electron density ρ е which in turn is correlated with the local tissue mass density ρ m . Thus since H (μ tissue ) ≈ ρ m , commonly the latter is deduced from measured relative attenuation coefficients assuming a piece-wise linear relation according to where ρ(H) is measured in CGS units g • cm -3 [17].…”
Section: Imaging Proceduresmentioning
confidence: 99%